Feasibility of the Korean-Advance Directives Among Community-Dwelling Elderly Persons. Issue 4 (July 2017) - Kim, Shinmi; Hong, Sun Woo; Kim, JinShil
Abstract : A newly developed Korean-Advance Directive (K-AD) consists of a value statement, treatment directives, and proxy appointment. It remains undetermined whether K-AD is applicable to community-dwelling persons (≥ aged 60 years). Using a descriptive study design, 275 elderly persons completed the K-AD (mean age = 77.28 ± 8.24 years). The most frequent value at the end of life was comfort dying, followed by no burden to family (23.6%). Among 4 K-AD treatment options, more than half had a preference for hospice care and had reluctance with aggressive treatment choices of cardiopulmonary resuscitation (76.4%), artificial ventilation (75.6%), and tube feeding (76.4%), with one-fifth having a desire for such options. All persons provided proxies, who were predominantly descendants (77.1%), followed by spouses (17.5%). For treatment preferences, men and those with no religion were more likely to receive life-sustaining treatments. These data support the K-AD as being applicable and acceptable among community-dwelling elderly persons; awareness of the K-AD in the community setting may facilitate future application when the need occurs.